Medialny obraz seksualnego kobiecego ciała a dobrostan obserwatora = The media image of the sexual female body and well-being of the observer - Niewiedział, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Review of the literature most often indicates that the image of sexual woman?s body presented by the media, affects the perception and functioning of the recipient. In the twentieth century, and now the image of the female body is created and used for various purposes, mainly consumer. In an individual process of perception of the female body the observer makes his own assessment, which is a result of its active interpretation of sensory data, context, attitudes and previously acquired knowledge. The process of active creation of the female body representation in the awareness of modern recipient is to include an additional element, which is the defense against manipulation. The article contains a reflections on ways to manipulate the sexual image of the female body in the media and the results of various studies about the awareness of this fact among the recipients.
Keywords: medialny obraz kobiecego ciała; techniki perswazji; dobrostan obserwatora; the media the image of the female body; persuasion techniques; well-being of the observer